Aluminium Nanofluids Stability: A Comparison between the Conventional Two-Step Fabrication Approach and the Controlled Sonication Bath Temperature Method. (27th October 2019) - Ali, Naser; Teixeira, Joao A.; Addali, Abdulmajid
Abstract : This study investigates the shelving stability of dispersed aluminium nanoparticles in water mixtures fabricated by the conventional and the controlled bath temperature two-step methods. The nanofluids were prepared with water of pH 9 and nanoparticles of 0.1–1.0 vol.%. A bath type ultrasonicator was employed for dispersing the nanoparticles into the base fluid. The sonication process, for all as-prepared samples, lasted for 4 hours and was either device bath temperature uncontrolled or controlled in the range of 10–60°C. Furthermore, the stability of the as-produced nanosuspensions was evaluated using the sedimentation photograph capturing method by capturing images at equal intervals of time for 12 hours then analysing the data based on the sample sedimentation height ratios. It was found that the sedimentation behaviour of the nanofluids fabricated via the controlled temperatures of less than 30°C was of dispersed sedimentation type, while those produced by the conventional method and the fixed temperatures of 30°C and higher were of flocculated sedimentation type. In addition, increasing the controlled sonication temperature has shown to increase the settling process of the sediments. Moreover, the rise in nanoparticle concentration was seen to reduce the variation in sedimentation height ratio between the fixed temperature samples. A comparison between the two fabrication methods has shown that the 30°C nanofluids had better short- and long-term stability than the conventionally produced suspensions.